Implementasi Program Student Led Conference (SLC) Dalam Pembelajaran Kolaboratif Siswa Guru dan Orang Tua - Agustyarini, Yhasinta; Ria Kusrini, Nurul Azizah; Ningrum, Rachmania Widya (Chalim Journal of Teaching and Learning, 2024)
This study investigated the effects of student-led conferences (SLC) on parents, instructors, and students at MI Progressive Al Musthofa Bangsal Mojokerto. A qualitative descriptive approach with a case study type of research was applied; this study involved observation, interviews, and document collection from 15 students, two teachers, and three parents of students in Class II Marwah. The Miles, Huberman & Saldana model was used in data analysis consisting of condensing, presenting, and making conclusions. The study's findings demonstrated that SLC gives parents, instructors, and students a chance to assess each other's development and identifies areas where kids need improvement. SLC helps teachers to understand students' individual development and gives parents a deeper understanding of their children's strengths, challenges, and dreams. With SLC, students can direct their learning by selecting engaging subjects to cover. In addition to encouraging individual study and subject exploration that aligns with students' interests, SLC can foster open communication between all parties and raise the shared accountability for kids' academic performance. Teachers and parents will be able to understand their pupils' learning experiences better, enabling them to offer more specialized help. By putting SLC into practice, educators may help students take charge of their education, foster a collaborative learning environment, and promote lifelong learning and academic advancement.